2016
DOI: 10.1097/mnm.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of thyroid cancer in focal hypermetabolic thyroid lesions

Abstract: Background The clinical significance of incidental thyroid abnormalities discovered in 18F-FDG PET/CT (FDG PET/CT) studies remains controversial. The objective of this large retrospective study was to a) determine the prevalence of focal FDG thyroid uptake on whole body FDG PET/CT studies performed for non-thyroid cancers and b) to test whether intense focal FDG thyroid uptake is associated with malignancy. Methods A total of 11,921 FDG PET/CT studies in 6,216 patients performed at our institution between 01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 23 publications
7
25
0
1
Order By: Relevance
“…Our retrospective analysis of clinical records showed a comparable incidence of thyroid malignancy or other thyroid disease in NF1 patients compared to previous studies in non-thyroid cancer patients [24-27]. Only one study by Ferner et al [7] described a case of FDG-PET-positive thyroid cancer in a population of NF1 patients ( n = 105; 1%) discovered through PET/CT.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our retrospective analysis of clinical records showed a comparable incidence of thyroid malignancy or other thyroid disease in NF1 patients compared to previous studies in non-thyroid cancer patients [24-27]. Only one study by Ferner et al [7] described a case of FDG-PET-positive thyroid cancer in a population of NF1 patients ( n = 105; 1%) discovered through PET/CT.…”
Section: Discussionsupporting
confidence: 67%
“…Demir et al [24], Bae et al [25], and Adas et al [26] showed lower percentages in non-thyroid cancer patients with a range between 1 and 3%. However, the most recent study with the largest population by Barrio et al [27] reported a comparable percentage of focal incidentaloma compared to this study (13.6%). Karantanis et al [28] reported a diffuse increased uptake in 2.9% of 4,732 non-thyroid cancer patients, which is comparable to our results.…”
Section: Discussionsupporting
confidence: 40%
“…Dual-time-point 18 F-FDG PET/CT and retention index were used in differential diagnosis of thyroid incidentaloma ( 28 ). Barrio et al ( 29 ) measured SUVmax, thyroid to background thyroid lesion SUVmax/thyroid background SUVmean (TL/TBG), thyroid to blood pool TL/blood pool SUVmean (BP), and thyroid to liver TL/liver SUVmean (L) ratios in benign and malignant lesions to test if intense focal 18 F-FDG thyroid uptake is associated with malignancy. These studies revealed various methods may significantly improve accuracy of PET/CT for differentiating benign from malignant focal thyroid lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It is not only caused by malignancy, but also by a variety of benign lesions such as nodular hyperplasia, Hurthle cell and follicular neoplasms, and even chronic lymphocytic thyroiditis. Barrio et al [ 16 ] demonstrated that 845/6212 (13.6%) patients with nonthyroid cancers had a thyroid incidentaloma, and 21 of the 98 patients who underwent fine-needle aspiration biopsy or thyroidectomy had malignant disease (21.4%), whereas the others (78.6%) had benign tumors. Increased FDG uptake in skeletal muscle and decreased uptake in the liver are also observed in a variety of pathological and physiological conditions.…”
Section: Discussionmentioning
confidence: 99%